Restriction of Islamic Civil Society Participation: Genealogy of Zakat Legal Politics and Its Centralized Management in Indonesia - Emzaed, Ali Murtadho; Aulia, Sidiq; Rosadhillah, Valencia Kirana; Sukti, Surya (Journal of Islamic Law, 2023)
This article analyzes the management of zakat (almsgiving) in Indonesia, focusing on the genealogy of legal politics and its relationship with state policies in centralizing zakat management. Given the variations in zakat management systems among Muslim countries, Indonesia’s direct participation in zakat management has provoked resistance within Islamic civil society. They do not desire any state intervention in zakat management, as it contradicts their longstanding practice before Indonesia’s independence. This article employs a historical approach and analyzes data using Fred W. Riggs’ prismatic legal theory. The authors find that the state’s argument for centralizing zakat management in Indonesia aims to optimize the efficient utilization of zakat funds. However, this policy hurts the participation of Islamic civil society in managing zakat according to their genealogical traditions. Therefore, the article argues that the state’s centralization of zakat management is inappropriate, as it overlooks the integral zakat practices rooted in Islamic civil society’s history and culture in Indonesia.